2018
DOI: 10.4178/epih.e2018024
|View full text |Cite
|
Sign up to set email alerts
|

Geographical distribution of health indicators related to snake bites and envenomation in Morocco between 1999 and 2013

Abstract: OBJECTIVESEnvenomation from snake bites is a significant cause of morbidity and mortality worldwide. The aim of this study was to describe the epidemiological features of snake bites in Morocco and to evaluate time-space trends in snake bite incidence, the mortality rate, and the case-fatality rate.METHODSThis is a retrospective study of snake bite cases reported to the Moroccan Poison Control Center between 1999 and 2013.RESULTSDuring the study period, 2,053 people were bitten by snakes in Morocco. Most victi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
3
8
0
Order By: Relevance
“…We consistently found that young to middle-aged males (age group = 15–44 years) were most at risk of snakebites, corroborating similar findings from Ghana [22, 23, 24], other parts of West Africa [15, 25, 26, 27, 47, 49, 50] and Africa in general [30, 34, 51, 52, 53]. Adolescent and young men in their twenties are among the most active and adventurous, albeit least cautious, section of rural African people [24, 27, 47, 54].…”
Section: Discussionsupporting
confidence: 86%
“…We consistently found that young to middle-aged males (age group = 15–44 years) were most at risk of snakebites, corroborating similar findings from Ghana [22, 23, 24], other parts of West Africa [15, 25, 26, 27, 47, 49, 50] and Africa in general [30, 34, 51, 52, 53]. Adolescent and young men in their twenties are among the most active and adventurous, albeit least cautious, section of rural African people [24, 27, 47, 54].…”
Section: Discussionsupporting
confidence: 86%
“…We consistently found that young to middle-aged men (age group = 15-44 years) were most at risk of snakebites, corroborating similar findings from Ghana [22, 23, 24], other parts of West Africa [15, 25, 26, 27, 44, 46, 47] and Africa in general [30, 34, 48, 49, 50]. Adolescent and young men in their twenties are among the most active and adventurous, albeit least cautious, section of rural African people [24, 27, 44, 51].…”
Section: Discussionsupporting
confidence: 85%
“…The data evidenced in the study corroborate with the results of several studies found in the literature in countries such as Morocco, India and Kenya where they show the frequency of men, rural workers and young age group with an average age of 26 years [18][19][20] .…”
Section: Discussionsupporting
confidence: 90%